Challenges Faced by the Second Language Learners: A Review - Aafia Sarwar Soomro (Sindh Journal of Linguistics, 2022)
The purpose of this review article is to identify the challenges faced by second language learners. It has been observed that English has the strongest position as a second or foreign language across the globe. Despite the prestigious status, learners are facing numerous challenges. This article gives a comprehensive review of the relevant literature from the last two decades, with special attention to different challenges in the way of second language learning. This review article investigates the various latest studies based on challenges faced by L2 learners. "Second language acquisition is a complex process, in many ways much more complex than first language acquisition, as the factors involved are numerous"(Ellis 2015,p. 17). While interpreting , it was established that challenges such as anxiety in L2 learners, interference of L1 on L2, socio-linguistic and socio-economic background of learners, structural differences between L1 and L2, flawed pedagogy, lack of interaction, practice, and motivation among second language learners have created major challenges in the way of successful second language learning and acquisition.